Research perspectives : thought and practice in music education - Thompson, Linda K.; Campbell, Mark Robin (Advances in music education research., 2009)
Research Perspectives: Thought and Practice in Music Education calls attention to various theoretical and methodological aspects within the expanding field of research in music education. Perspectives presented in this volume offer readers a host of ideas and practices that range from international and historical to empirical and philosophical. Of special interest is a set of invited essays. Collectively, these essays illuminate our understanding of the peer review process, the importance of artistic vision in research and education, and the notion of complementarity - a recognition of the validity of diversity of thought and practice in music education research.The studies in Part 1 of Research Perspectives include early childhood musical development, an international comparison of early childhood preservice teacher knowledge and skills, and a psychohistoric examination of developmentally appropriate practice. Part II is comprised of studies focused on psychometrics of motivation, and professional development of practicing music educators. This volume is a significant addition to the libraries of Colleges of Education and Schools of Music, as well as an important reference for music scholars and educators, researchers, and graduate students who are concerned with advancing both the scope and quality of research in the study of music teaching and learning.